Inflammatory Markers and Risk of Parkinson’s Disease: A Population-Based Analysis - Hongping Wang; Wenqiang Li; Qun Lai; Qian Huang; Hao Ding; Zhiping Deng (Parkinson's Disease)
Conclusions: There was a significant association between elevated levels of NLR, PLR, and PD risk, while LMR, SIRI, and SII were not statistically significant. It suggests that NLR or PLR could be used to screen people at risk of PD at an early stage. It is essential to conduct more large-scale prospective studies to investigate the role that NLR and PLR play in PD.